Different activation of MAPKs and Akt/GSK3β after preload vs. afterload elevation. (21st March 2022) - Hartmann, Nico; Preuß, Lena; Mohamed, Belal A.; Schnelle, Moritz; Renner, Andre; Hasenfuß, Gerd; Toischer, Karl
Abstract: Aims: Pressure overload (PO) and volume overload (VO) lead to concentric or eccentric hypertrophy. Previously, we could show that activation of signalling cascades differ in in vivo mouse models. Activation of these signal cascades could either be induced by intrinsic load sensing or neuro‐endocrine substances like catecholamines or the renin‐angiotensin‐aldosterone system. Methods and results: We therefore analysed the activation of classical cardiac signal pathways [mitogen‐activated protein kinases (MAPKs) (ERK, p38, and JNK) and Akt‐GSK3β] in in vitro of mechanical overload (ejecting heart model, rabbit and human isolated muscle strips). Selective elevation of preload in vitro increased AKT and GSK3β phosphorylation after 15 min in isolated rabbit muscles strips (AKT 49%, GSK3β 26%, P  < 0.05) and in mouse ejecting hearts (AKT 51%, GSK49%, P  < 0.05), whereas phosphorylation of MAPKs was not influenced by increased preload. Selective elevation of afterload revealed an increase in ERK phosphorylation in the ejecting heart (43%, P  < 0.05), but not in AKT, GSK3β, and the other MAPKs. Elevation of preload and afterload in the ejecting heart induced a significant phosphorylation of ERK (95%, P  < 0.001) and showed a moderate increased AKT ( P  = 0.14) and GSK3β ( P  = 0.21) phosphorylation, which did not reach significance. Preload and afterload elevation in muscles strips from human failing hearts showed neither AKT nor ERK phosphorylation changes. Conclusions: Our data show that preload activates the AKT–GSK3β and afterload the ERK pathway in vitro, indicating an intrinsic mechanism independent of endocrine signalling.